Abordagem Multivariada para Imputação de Temperatura Média na Região Amazônica baseada em Estações Meteorológicas e Dados de Reanálise ERA5-Land - Dias, Jean Arthur Costa; Alves, André Vinicius N.; Negreiros, Waldemiro J. A. G.; Novais, Rodrigo Gonçalves; Oliveira, Fernando Luiz Cyrino; Tamasauskas, Leonardo de O.; Guimarães, Pedro H. do V.; Figueiredo, Karla; Costa, Gabriel B.; Gomes, Marivan S.; Seruffo, Marcos César da Rocha (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA), 2026)
This study investigates the imputation of missing values in mean air temperature time series in the state of Pará, Brazil, by integrating observational data from INMET and the ERA5-Land reanalysis. A multivariate non-linear approach based on the MissForest algorithm was developed and compared with models using only station data and with linear interpolation. The evaluation employed synthetic gaps together with the RMSE, MAE, and MAE in quantile 99 metrics. The results indicate that the inclusion of ERA5-Land reduced RMSE to 0.664–0.744 °C, MAE to 0.509–0.569 °C, and ∆P 99 to 0.909–1.013 °C, while increasing model stability and outperforming the other strategies, thus supporting the methodological consistency of the approach for tropical climate time series.